Analyze of pilot reuse with achievable sum rate for massive MIMO cellular uplink - Salh, A.; Audah, L.; M. Shah, N. S.; Hamzah, S. A. (Asian Research Publishing Network (ARPN), 2017)
The last ten years have seen important developments of massive multi-input multi-output (MIMO) in wireless communication. Massive MIMO has currently been presented in the 5G wireless standards. The number of terminals is increasing with additional appliances. At the same time, high transmission sum rates and communication reliability are required. Moreover, the multi-cell MMSE scheme, which includes an uplink MMSE and MRT decoders. Furthermore, this paper focuses how the MMSE activities all obtainable pilots for interference suppression. Specifically, this paper investigates the spectral efficiency of the massive MIMO, pilot contamination, which MMSE exploits all available pilots for interference suppression, and estimated locally at every BS, to actively suppress both intra-cell and inter-cell interference. Consequently, the average sum rate is proportional with SINR, using the linear scheme all of MMSE, ZF and optimal MMSE, while the sum rate is reverse proportional with linear decoding MRT. Then, when the number of base stations increases, the linear schemes MMSE, ZF and optimal MMSE have more convergence, while when the number of BS decreases the linear decoding schemes only have convergence except for MRT. However, at high SNR a higher number of antennas achieve better than a low number of antennas.